Math-ish : finding creativity, diversity, and meaning in mathematics - Boaler, Jo, 1964- (HarperOne, an imprint of HarperCollinsPublishers, 2024)
Mathematics is a fundamental part of life, yet every one of us has a unique relationship with learning and understanding the subject. Working with numbers may inspire confidence in our abilities or provoke anxiety and trepidation. Stanford researcher, mathematics education professor, and the leading expert on math learning Dr. Jo Boaler argues that our differences are the key to unlocking our greatest mathematics potential. In Math-ish, Boaler shares new neuroscientific research on how embracing the concept of "math-ish"--a theory of mathematics as it exists in the real world--changes the way we think about mathematics, data, and ourselves. When we can see the value of diversity among people and multi-faceted approaches to learning math, we are free to truly flourish.